1998
DOI: 10.1177/0310057x9802600504
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Fluid-Vasopressor Regimens Used to Prevent Hypotension during Subarachnoid Anaesthesia in the Elderly

Abstract: We aimed to compare the efficacy of fluid preloading with two recently recommended fluid-vasopressor regimens for maintaining blood pressure during subarachnoid anaesthesia in the elderly. Sixty elderly patients requiring surgery for traumatic hip fractures received subarachnoid anaesthesia using 0.05 ml/kg of 0.5% heavy bupivacaine. Hypotension, i.e. systolic arterial pressure <75% of baseline, was prevented or treated by: A—normal saline 16 ml/kg plus intravenous ephedrine boluses (0.1 mg/kg); B—normal sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
3
18
1
Order By: Relevance
“…An association between hypotension after spinal anaesthesia induction and hypertension in the past medical history has also been previously shown. 21 The effect of increased age on the occurrence of hypotension was reported several years ago 30 and has been confirmed by others 1,31 as well as shown in the present study. The minimal improvement in accuracy when definition 1 (67%) was compared with definition 4 (68%) shows a limitation in detecting IOH based on documented BP alone.…”
Section: Table 3 (Continued)supporting
confidence: 92%
“…An association between hypotension after spinal anaesthesia induction and hypertension in the past medical history has also been previously shown. 21 The effect of increased age on the occurrence of hypotension was reported several years ago 30 and has been confirmed by others 1,31 as well as shown in the present study. The minimal improvement in accuracy when definition 1 (67%) was compared with definition 4 (68%) shows a limitation in detecting IOH based on documented BP alone.…”
Section: Table 3 (Continued)supporting
confidence: 92%
“…Therefore, optimizing cardiac preload may be fundamental to preventing spinal hypotension and organ dysfunction in elderly patients. However, to date, there are many literatures debating the type and amount of fluid preload[11][13]. The present study showed that a fluid preload of 8 mL/kg increased cardiac output.…”
Section: Discussionsupporting
confidence: 44%
“…To prevent spinal anesthesia-induced hypotension, intravenous fluid preload is commonly used. However, based on previous studies in which only blood pressure and heart rate were used to assess the efficacy of fluid preload, the type and amount of fluid preload for preventing spinal hypotension are still controversial[11]-[13].…”
Section: Introductionmentioning
confidence: 99%
“…Potential complications which may have limited its use include hypotension and spinal haematoma. There is new evidence to support a number of interventions aiming to reduce the incidence of hypotension 62 . ‐ 66 , 68 In the recent Pulmonary Embolism Prevention trial, 56 no occurrences of spinal haematoma were documented in the 4603 hip‐fracture patients who received regional anaesthesia (including those with and without aspirin and other anticoagulant therapy).…”
Section: Discussionmentioning
confidence: 99%